Cloning and analysis of pyrG gene encoding orotidine 5-Monophosphate decarboxylase of aspergillus oryzaeStrain S1 - Selina Oh Siew Ling,; Leong, Jiun Min; Abdul Munir Abdul Murad,; Nor Muhammad Mahadi,; Farah Diba Abu Bakar, (Universiti Kebangsaan Malaysia, 2011)
In this study, the pyrG gene which encodes for orotidine 5-monophosphate decarboxylase (OMP decarboxylase) of Aspergillus oryzae strain S1 was cloned and analysed. This 1.8kb A. oryzae pyrG encompasses the 5’-regulatory flanking region (465 bp), open reading frame (899 bp) and 3’-regulatory region (475 bp). The pyrG contained one intron at position 623-687 bp based on the AUGUSTUS and FGENESH (SoftBerry) analysis corresponding to the intron present in the pyrG of A. oryzae (Accession Number: Y13811). In silico analysis showed that the enzyme encoded by the A. oryzae S1 pyrG gene has a theoretical molecular weight of 30.28 kDa and theoretical pI value of 5.92. This enzyme is hydrophilic, located in a region outside of the transmembrane and it functions in the cytoplasm. Five motives such as N-glycosylation site, protein kinase C (PKC) phosphorylation site, casein kinase II (CK-2) phosphorylation site, N-myristolation site and orotidine 5-monophoshate decarboxylase active site have been identified in the pyrG amino acid sequence. The three dimensional structure of this enzyme generated via protein homology modeling using the bioinformatic software, Swiss Model, shows that OMP decarboxylase is a protein with an α/ß barrel structure possessing 8 ß-strands surrounded by 9 α-helices. The amino acid residues involved in the active site have been identified and it is located on one of the ß-strands. The pyrG DNA sequence will be used for the complementation of a pyrG auxotroph mutant of A. oryzae.